Ethnographic expedition in Bolnisi community (The report of the ethnographic expedition in 2019) - Shavianidze, Davit (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2019)
During the students expedition of Akaki Tsereteli State University of the faculty of humanities we have conducted ethnographic research and have interviewed the people in Bolnisi, Pitareti, Kveshi, Ratevani, Akaurta, Kianeti, Kazreti, Balicha, Mashavera (July, 2019). Enemy invasions were followed by the losing Georgian territories, emptying villages and resettlement of the foreign nations o the Georgian lands. Only the following villages are survived from the villages that existed in the beginning of XVIII c: Musopriani, Itsria, Balakhauri, Mukhrana and Mtsknetia. The villages are registered with the Georgian names, although some of them are named by their Azerbaijanian names (Bovnisi - Ekaterinenpildi -Luxemburg -city Bolnisi; Khachini - vil. Bolnisi; Injaoghli - middle Bolnisi; Kapanakhchi - Lower Bolnisi; Tandzia - Tandzia; Tamarisi - Tamarisi; Kazreti - Kazreti; Ratevani - Ratevani; Salalari - Zvareti; Rachisubani -Rachisubani; Japarlo - Samtredo; Migitlo - Vanati; Tsitelsopeli - Khatisopeli; Samtsevrisi -Samtsevrisi; Poladauri -Poladauri; Sarachlo - Mamkhuti; Kvemo Koshakilisi - Kvemo Arkevani, Zemo Koshakilisi - Zemo Arkevani; Patara Ahmedlo - Khataveti; Darbazi -Darbazi; Zemo Gulaveri - Tsipori; Demurlo - Khakhalajvari; Kibirjiki - Chreshi; Akaurta - Akaurta; Dzveli kveshi -Dzveli kveshi; Arakeli Dzedznariani; Musopriani-Potskhveriani; Kvemo Gulaveri - Geta; Bektakari - Bertakari; Karadashi - Itsria; Senebi - Senebi; Balichi - Balichi; Mughanlo - Parizi; Lagiri- Tsurtavi; Pakhralo - Talaveri; Patara Darbazi - Patara Darbazi; Imirasani - Savaneti; Kveshi - Kveshi; Abdalo - Javshaniani; Kianeti - Kianeti, Mushevani -Mushevani, Karatikani - Sabereti; Arakhlo - Nakhiduri; Asankhojalo - Khidiskhuri; Siskala - Balakhauri; Tashtikulari - Mukhrana; Kochulo - Chapala; Asmalari - Mtskneti; Tapani - Disveli; Tsughrughasheni - Tsughrughasheni). We have rarely found villages settled by Georgians as a majority. The diversional information about etnic identity of the cultural levels, mentality, traditions, agriculture and the remains of the primary habitat are reflected in the obtained data - in the place names and the lexical units („Tamarisarkhi [Tamar’s Channel]“; „Berebis Tskhali water of the monks]“; „Batonis Tskali [the water of the lord]”; „or sakdre“; „Shushkhuna Tskaro” [sparkling spring]“; „Tsitelitskaro [red spring]”; „Pantiani [place where wild pear is grown]“; „velebi [fields]“; „Gokhebi“; „Javakhi“; „Mija“; „Akvaneba“; „Ojakhisdambrunebeli kali [the woman who got the family back]“; „Kargi Patardzali [good bride]“; „Vartsl-burjis Kali“; „Namdvilojakhi” [the real family]; „Garetuli bebia [grandma who is out]“; „Komagoba [supporting]“; „Bediti [vain]“; „Ghrmasopeli [deep village]” ; „Moichita [becoming colorful]”; „Tserebaddadgma“…). The people from the different regions of Georgia were sharing their own localregional rules to each other after their resettlement in Bolnisi. It is also noteworthy that the local Georgian rituals are being forgotten. The holiday of “Lamproba” is never held anymore. The family name suffix, that was peculiarity of the subdivisions of Svan families was replaced with the suffix “-anti” After the resettlement in Bolnisi. During our fieldwork we have recorded the epitaphs of the praise genre, about the private life, as well as describing the attitude towards the private life, behavior in the family and in the rest of society, towards the native country, etc. We have also checked the list of the family names that have been living earlier in the particular villages. We have recorded the text about the traditional methods of folk medicine and social upbringing. We think that the integration of the representatives of the not Georgian ethnos and the local Georgians living in Bolnisi municipality villages should deserve more attention.